Thalidomide decreases high glucose-induced extracellular matrix protein synthesis in mesangial cells via the AMPK pathway - Zhang, Hong-Xia (Exp Ther Med, 2019)
A previous study demonstrated the renal-protective effect of thalidomide (Thd) in diabetic nephropathy rats through the activation of the adenosine monophosphate-activated protein kinase (AMPK) and inhibition of the nuclear factor κB (NF-κB)/monocyte chemoattractant protein-1 (MCP-1) and transforming growth factor (TGF)-β1/mothers against decapentaplegic homolog signaling pathways. The association between AMPK inactivation and high glucose (HG)-induced meningeal cell (MC) proliferation and extracellular matrix (ECM) accumulation via NF-κB and TGF-β1 signaling remains unknown. The aim of the current study was to demonstrate the effects of Thd on cell proliferation and ECM expression in HG-cultured MCs and the underlying mechanisms. HG-cultured human MCs were treated with Thd. Cell proliferation was measured by MTT assay and quantification of cell proliferation was based on the measurement of bromodeoxyuridine incorporation. The differences in TGF-β1, fibronectin and MCP-1 protein expression levels were detected via ELISA and western blot analysis. The AMPK signaling pathway was also examined by western blot analysis in MCs. Compound C, an AMPK inhibitor and AICAR (5-aminoimidazole-4-carboxamide 1β-D-ribofuranoside), an AMPK agonist, were used to analyze the functional role of AMPK in MCs. Cell proliferation was significantly decreased in HG-cultured MCs following treatment with high concentrations of Thd (100 and 200 µg/ml) for 24 h compared with the HG-cultured MC group. Thd suppressed the inflammatory processes in HG-induced MCs. These effects were partially mediated through the activation of AMPK and inhibition of the NF-κB/MCP-1 signaling pathways. Taken together, these results suggest that Thd may have therapeutic potential in diabetic renal injury via the AMPK signaling pathway.